Is there a pre-Cretaceous source rock in the Colombia Putumayo Basin? Clues from a study of crude oils by conventional and high resolution geochemical methods - M. MARTÍNEZ; R. MÁRQUEZ; G. GUTIÉRREZ; L. MAYA; C. MORA; W. GUZMÁN; J.M. MOLDOWAN (Geologica Acta, 2014)
A geochemical characterization of sixteen crude oil samples from the Putumayo Basin, southern Colombia, was carried out. This basin is located to the north of Ecuador’s Oriente Basin, one of the most prolific hydrocarbon basins in South America. Regardless of the fact that these two basins seem to share the same geological evolution, the volume of hydrocarbon reserves found in the Oriente Basin is five times greater than in the Putumayo Basin. This represents an exploratory opportunity to the extent that a better understanding of the petroleum system processes in the Putumayo Basin can be achieved. Newly available geochemical technology shows evidence that these crude oils originated from Late Cretaceous source rocks. The novel application of an age-related biomarker, the C25- highly branched isoprenoid, has constrained the age of the principal source of all these oils as Late Cretaceous or younger. Advanced geochemical technologies, such as compound specific isotope analyses of biomarkers (CSIA-B) and diamondoids (CSIA-D), and quantitative extended diamondoid analysis (QEDA), have confirmed, repeatedly, that the oil samples are all related to the same source with minor facies variations. The integration of these results with geological data suggests the presence of a very efficient petroleum system, characterized by an alternating sequence of soçurce and reservoir rocks. Thermal maturity of the oils from biomarker and diamondoid parameters ranges from well before the peak of hydrocarbon expulsion to the beginning of the late hydrocarbon generation phase. The aerial distribution of these maturity parameters suggests the existence of two, or possibly three, pods of active source rocks, located to the southwest and to the east of the basin, and possibly to the north. This would modify the classic hydrocarbon migration model for the Putumayo Basin, increasing the hydrocarbon potential of the basin. Given the low level of thermal maturity documented in the Cretaceous sequence that has been drilled, the possibility to evaluate the presence of a very reactive kerogen with hydrocarbon expulsion thresholds at lower temperatures is proposed.